Technology-Based Management of Learners in the Society 5.0 Context: Opportunities for Improving Islamic Educational Institutions in Indonesia - Isel, Selfia Zainur; Doa Salsabil, Maulidnear; Zahara, Aulia; Aulia Redisti, Tia; Hidayatullah, Rully; Zulmasri, Zulmasri (International Journal of Islamic Teaching and Learning, 2025)
Learner management that integrates technology can improve interactions between teachers and learners, enable active learning, and help realize educational goals. This research aims to explore the application of technology-based learner management concepts in improving the quality of services of Islamic education institutions in the era of Society 5.0. The research was conducted using a qualitative approach and a literature study. Literature studies were performed on several articles and books that examine educational management, both concepts and their application in academic institutions. Data analysis is carried out with the stages of editing data that will be used as material for analysis, organizing data by research objectives, finding a theme that needs to be confirmed with previous studies, and concluding to reveal new concepts in learner management. The results of this study found four basic principles in technology-based learner management in Islamic educational institutions, namely: i) utilization of digital platforms, ii) effective and efficient management of learners, iii) making it easier for learners to achieve learning goals, and iv) collaboration of learning environments to support the success of learners in pursuing education within a specific time. The application of digital management concepts can create convenience in learner governance, especially in recording learner data, mutations, and promotions, as well as special services in developing the potential and interests of learners. In addition, this study found that using technology in learner management in Islamic educational institutions can improve the quality of education while maintaining Islamic values in every aspect of learning. This study can be a reference for future researchers researching education management in various contexts and issues.